Pola Pengelolaan Sumberdaya Alam Pesisir yang Berkelanjutan - Abdi Muliawan Harahap; R. Hamdani Harahap; Heri Kusmanto (Universitas Medan Area, 2021)
The potential of coastal natural resources in Indonesia is so diverse and should be able to contribute to the economy of the people in Indonesia. The utilization of coastal natural resources depends on how the natural resource management patterns are. Location Desa Sei Nagalawan has coastal natural resources which are also managed by the community for their economic interests. This research was conducted with a mixed method of qualitative and quantitative methods to find out how the pattern of coastal natural resource management in Sei Nagalawan Village. This study wants to see whether the management carried out by the community includes management that adheres to the principles of sustainable development. The results obtained from this study are that the fishing communities who live in the coastal area of Sei Nagalawan Village, Perbaungan District, Serdang Bedagai Regency have an organized management pattern. Management that is done is by taking marine life such as cuttlefish, shrimp, crab and fish which is done in the traditional way. In addition, coastal natural resources are also managed as tourist attractions. The coastal area in Sei Nagalawan Village has mangrove land which is well cared for and managed by the community. Management that is done is by processing the leaves and mangrove fruit for food.